Effects of spironolactone on extrasystoles and heart rate variability in haemodialysis patients: a randomised crossover trial - Michael Eklund; Olof Hellberg; Hans Furuland; Yang Cao; Erik Nilsson (Upsala Journal of Medical Sciences, 2021)
Background: Spironolactone treatment reduces mortality in haemodialysis (HD) patients. The objective of this study was to evaluate if spironolactone affects cardiac electric activity in this population. Methods: Participants were randomised to start with spironolactone 50 mg daily or observation (12 weeks) with subsequent washout (6 weeks) and crossover to the other intervention (12 weeks). Long-term electrocardiograms were recorded and assessed with blinding to treatment. The primary outcome was premature ventricular complexes (PVC), and secondary outcomes were atrial premature contractions (APC) and heart rate variability (HRV). Results: Thirty participants were recruited, and data for 16 participants were included in the analysis. Treatment was associated with an increase in PVCs by 9.7 [95% confidence interval (CI): 1.5 to 18] h−1. HRV time-domain variables increased during treatment, the standard deviation of all beat-to-beat intervals by 18 (95% CI: 3.3 to 32) milliseconds (ms) and the standard deviation of the averages of beat-to-beat intervals in all 5-min segments of the entire recording by 16 (95% CI: 1.5 to 30) ms. There were no significant differences in other variables. Conclusion: Spironolactone treatment increases PVCs in HD, indicating a possible proarrhythmic effect. However, improved cardiac autonomic function, as indicated by an increased HRV, may contribute to the survival benefit from spironolactone treatment in HD patients.